2010
DOI: 10.1103/physreva.81.023601
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of two-dimensional fast-rotating ultracold fermionic atoms near unitarity

Abstract: By analyzing vortex lattices, re-entrant Cooper pairing, and Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) states in a single theoretical framework, we explore how vortices and spin textures join to protect superconductivity against large magnetic fields. We use a rapidly rotating ultracold gas of fermionic atoms near unitarity as a model system amenable to experimental exploration and discover a hierarchy of spin-polarized and FFLO phases in which a metal or a band insulator of unpaired particles coexists with a sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…An effect of rotation on the FFLO state has been studied in the context of cold Fermi gases [27][28][29] as well as in mesoscopic superconductors where the magnetic field plays an equivalent role to the rotation [28,30,31]. It has been shown that the nucleation of vortex in the FFLO superfluid gives rise to intriguing phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…An effect of rotation on the FFLO state has been studied in the context of cold Fermi gases [27][28][29] as well as in mesoscopic superconductors where the magnetic field plays an equivalent role to the rotation [28,30,31]. It has been shown that the nucleation of vortex in the FFLO superfluid gives rise to intriguing phenomena.…”
Section: Introductionmentioning
confidence: 99%